Use Of The Kitabisa.Com Application In The Implementation (Crowdfunding) In Indonesia - cindy fadilah nasution; Tri Kurniawati Retnaningsih*; Ita Rodiah (IAIN Palopo, 2022)
Social movements aim at victims who experience accidents or difficulties due to loss of property, life or residence. The role of the community in this area is of course to provide assistance by collecting donations or assistance. They coordinate their practices in the fundraising process, starting from collecting, calculating, managing, and distributing aid to disaster victims, with multi-stakeholder collaboration to carry out fundraising activities. the existence of the Internet not only helps people's lives, but changes them slowly and gradually. This research uses the method of literature review (library research) in which the author collects data obtained from many reliable sources, such as through books, journals and other written sources that can support the discussion of the contents of this article. Especially since the internet is now easily accessible for mobile internet use with smartphones as well. Convenience is shown when it offers convenience that is usually carried out directly and now can also be used indirectly. Fundraising is a way of pooling money from people online without face-to-face contact. Crowdfunding is relatively simple in its process. Entrepreneurs, also known as project founders in the crowdfunding process, publish their project ideas on online fundraising platforms, as well as potential investors interested in the project. The aim of the fundraising platform is to help entrepreneurs create semi-structured websites to promote their ideas and provide opportunities for consumers to acquire goods or services before the marketing process